2014
DOI: 10.1007/s13105-014-0339-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of resveratrol against doxorubicin-induced cardiac toxicity and fibrosis in male experimental rats

Abstract: The possible effectiveness of resveratrol, a polyphenol present in different plants comprising berries, grapes and peanuts, on the prevention of doxorubicin-induced cardiac toxicity and fibrosis was investigated. Forty adult male Wistar albino rats were divided into four groups. Group I received normal saline, group II gavaged with resveratrol (20 mg/kg, daily for 4 weeks), group III received doxorubicin (2.5 mg/kg i.p. in six injections for 2 weeks; accumulative dose of 15 mg/kg), and group IV received doxoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 45 publications
10
73
0
Order By: Relevance
“…Here, we found a marked reduction in left ventricular end-diastolic posterior wall thickness, ejection fraction, and fractional shortening percentage in Dox-treated rats, concomitantly with increased cardiomyocyte membrane permeability and serum LDH concentration. This was consistent with previous studies in several animal models [8,19,33]. However, upregulation of miR-29b was effective in improving cardiac function.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we found a marked reduction in left ventricular end-diastolic posterior wall thickness, ejection fraction, and fractional shortening percentage in Dox-treated rats, concomitantly with increased cardiomyocyte membrane permeability and serum LDH concentration. This was consistent with previous studies in several animal models [8,19,33]. However, upregulation of miR-29b was effective in improving cardiac function.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, upregulating the mRNA level of TIMPs or downregulating the mRNA levels of TGFβ-1 and MMPs may inhibit fibrosis. Fibrosis is reportedly induced by ADR in myocardial tissue (31), which is supported by the present study findings. The present results indicate that EP can alleviate ADR-induced fibrosis by upregulating the mRNA levels of MMPs relative to those of TIMPs as well as downregulating the mRNA levels of TGFβ-1 and TIMPs, since it was observed that rats in the ADR + EP group had a lower collagen volume fraction in myocardial tissue, lower mRNA levels of TGFβ-1, TIMP1, TIMP2, Colla1 and Colla3, and higher ratios of MMP9/TIMP1 and MMP2/TIMP2, compared with those in the ADR group.…”
Section: Discussionsupporting
confidence: 92%
“…doxorubicin, sunitinib, cisplatin, and trastuzumab) have been demonstrated to cause severe acute and chronic cardiotoxic effects that may lead to cardiac dysfunction and heart failure [202,203]. A number of studies have demonstrated that resveratrol protects against doxorubicin-induced cardiotoxicity in a variety of animal models (Table 5) [261][262][263][264][265][266]. Multiple mechanisms have also been proposed to explain the protective effect of resveratrol against doxorubicin-induced cardiotoxicity.…”
Section: Chemotherapy-induced Cardiotoxicitymentioning
confidence: 99%